Teaching Speaking Through Role Playing Method Viewed From Students’ Interest - Hamid Asman (Penerbit STKIP PGRI Bangkalan, 2016)
This experimental study was carried out at the English Education Department of IKIP-PGRI Pontianak in the Academic Year of 2016/2017. The population was the first semester students and the sample consisted of two classes. The experimental group was treated by using role playing; while the control group was treated by using Metacognitive instruction method. The sampling technique used was cluster random sampling. The instruments used to collect the data were questionnaire and speaking test. The data were analyzed by using multifactor analysis of variance (ANOVA 2X2) and tukey test. The findings were: (1) Role playing was more effective than Metacognitive instruction to teach speaking; (2) the students with high interest have better speaking skill; and (3) there was an interaction between teaching methods and students’ interest. It can be concluded that Role playing is an effective way to teach speaking.